PENGARUH IKLIM ORGANISASI TERHADAP PRESTASI KERJA PEGAWAI DINAS PERINDUSTRIAN PERDAGANGAN KOTA SAMARINDA - Herta Sudyanti Utami (Jurnal Paradigma (JP), 2017)
The discussion of this writing was focus on the enhancement of employee achievement in Trade and Industry Department of Samarinda. It was pursued through responsibility, work quality, reward, and team work. This achievement influences to organization objectives.